Assessment of the Phytochemical Constituents of Methanol Extract of Ereromastax Polysperma Leaves and its Effect on the Hematological Indices in Albino Rats - Idung, Victor Hogan; Okon, Grace Asukwo; Asiwe, Nicholas (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2024)
The study investigated the effects of chronic administration of methanol extract of Eremomastax polysperma on the hematological parameters of albino rats. The rats were administered daily and orally for 14 days, with water as a control. On day 15, they were anesthetized using chloroform and blood was withdrawn from the heart through cardiac puncture into ethylene diamine tetra acetic acid (EDTA) specimen bottles. The phytochemical screening of crude methanolic extracts revealed the presence of secondary metabolites such as alkaloids, saponin, flavonoids, and cardiac glycosides. The statistical test employed was Analysis of Variance (ANOVA), with a predetermined significance level of p<0.05 and p<0.01. The ANOVA analysis revealed significant differences in red blood cell count (RBC), hemoglobin (HGB) percentages among the control group and the treatment groups of 500mg/kg and 1500mg/kg. The hematological evaluation showed a significant difference in RBC, HGB, and HCT, and a significant decrease in mean corpuscular hemoglobin concentration (MCHC) with increasing doses of the extract. The results suggest that E. polysperma has anti-inflammatory, antimalarial, antimicrobial, cytotoxic, antispasmodic, and pharmacological effects, potentially aiding in disease treatment.